EXPERIMENTAL PERFORMANCE OF PHOTOVOLTAIC/SOLAR THERMAL PANELS WITH WATER AND PCM COOLING SYSTEM - Naemsai, T.; Phetsongkram, P.; Kongboon, P.; Jareanjit, J. (Journal of Advanced Manufacturing Technology (JAMT), 2022)
This article evaluated the thermal and electrical efficiencies of different photovoltaic (PV) panels cooled by water-based systems and phase change material (PCM) under functional conditions to attain the appropriate operating state of the PV panel. Conventional PV panels, PCM-based PV systems, and water-based PCM PV systems were experimentally investigated. The copper tube arrangement was inserted within the aluminum container attached to the PV panel's bottom. The fully refined paraffin wax of 20 kg was filled inside the container. The experiment was presented at five volumetric flow rates: 1, 2, 3, 4, and 5 L/min. The electrical and thermal efficiencies are set as an indicator. For the experimental results, thermal efficiency rose gradually as the volumetric flow rate increased in the PV panel case cooled by the water-based system with PCM. Electrical efficiency progressively rose later, although it somewhat dropped. The PV panel's average electrical efficiency with a volumetric flow rate of 3 L/min was 27.5% that higher than the other cooling systems. Besides, it also offered an average thermal efficiency of 44%. Therefore, the water-based system with PCM at a volumetric flow rate of 3 L/min had a more appropriate application for the actual operation than the other cooling systems.